In vitro modeling of isoniazid resistance mechanisms in Mycobacterium tuberculosis H37Rv - Dokrungkoon, Thanadon; Tulyaprawat, Orawan; Suwannakarn, Kamol; Ngamskulrungroj, Popchai (Frontiers in Microbiology, 2023)
Introduction Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis, has been a global threat to human beings for several decades. Treating tuberculosis has become more difficult as the prevalence of drug-resistant tuberculosis has increased globally. Evidence suggests that the comprehensive landscape of resistance mechanisms in MTB is ambiguous. More importantly, little is known regarding the series of events connected to resistance mechanisms in MTB before exposure to anti-TB drugs, during exposure to the drugs, and finally, when the MTB becomes resistant after exposure, upon analyses of its genome. Methods We used the wild-type strain of MTB (H37Rv) in an in vitro model for generating induced resistance using a sub-inhibitory concentration of isoniazid, and the generated resistance-associated variants (RAVs) were identified using the whole genome sequencing method. Results The detection of an inhA promoter mutation (fabG1−15C>T), which results in increased production of InhA protein, was found to be a major mechanism for developing resistance to isoniazid in the first place. We observed adaptation of MTB resistance mechanisms in high isoniazid stress by alteration and abolishment of KatG due to the detection of katG S315N, the common region of mutation that confers isoniazid resistance, along with katG K414N, katG N138S, and katG A162E. Furthermore, we detected the ahpC−72C>T and ahpC 21C>A mutations, but further investigation is needed to determine their role in compensating for the loss of KatG activity. Discussion This suggests that increased InhA production is the main mechanism where there are low levels of isoniazid, whereas the alteration of KatG was found to be utilized in mycobacterium with a high concentration of isoniazid. Our work demonstrates that this in vitro approach of generating induced resistance could provide clinically relevant information after the fabG1−15C>T mutation, which is the common mutation found in clinical isolates. Moreover, other mutations detected in this work can also be found in clinical isolates. These findings may shed light on the impact of isoniazid in generating RAV and the resistance mechanism scenario that mycobacterium used under various isoniazid-pressuring conditions. More research is needed to understand better the role of RAV and mechanical resistance events within the mycobacterium genome in promoting a promising drug prediction platform that could lead to the right treatment for patients with MDR-TB and XDR-TB.